E-COMMERCE WEBSITE - PROF. MORE R.S.; SNEHA MANE; KHUTEJA SHAIKH (International Journal of Innovations in Engineering Research and Technology, 2021)
The business to consumer aspect of electronic commerce (e-commerce) is the most visible business use of the Word Wide Web. Theprimary goal of an e-commerce site is to sell goods and services online.This project is a web based shopping system for an existing shop. The project objective is to deliver the online shopping application.This project is an attempt to provide the advantages of online shopping to customers of a real shop. It helps buying the products in the shop anywhere through internet by using a web site. Thus the customer will get the service of online shopping and home delivery from this shop. This system can be implemented to Sai Supermarket in the locality.If shops are providing an online portal where their customers can enjoy easy shoppingfrom anywhere, the shops won’t be losing any more customers to the trending online shops such asflipkartoreBay.Sincetheapplicationisavailableinthegivensiteitiseasilyaccessibleand always available.